Genetic and toxinological divergence among populations of Tityus trivittatus Kraepelin, 1898 (Scorpiones: Buthidae) inhabiting Paraguay and Argentina. - Adolfo Borges; Antonieta Rojas de Arias; Sabrina de Almeida Lima; Bruno Lomonte; Cecilia Díaz; Carlos Chávez-Olórtegui; Matthew R Graham; Evanguedes Kalapothakis; Cathia Coronel; Adolfo R de Roodt (Public Library of Science (PLoS), 2020)
Envenoming by scorpions in genus Tityus is a public health problem in Tropical America. One of the most medically significant species is Tityus trivittatus, which is known to occur from southwest Brazil to central-northern and eastern Argentina. In this work, we studied the lethality, composition, antigenicity, and enzymatic activity of venom from a T. trivittatus population found further north in urban areas of eastern Paraguay, where it has caused serious envenomation of children. Our results indicate that the population is of medical importance as it produces a potently toxic venom with an LD50 around 1.19 mg/kg. Venom neutralization in preliminary mouse bioassays was complete when using Brazilian anti-T. serrulatus antivenom but only partial when using Argentinean anti-T. trivittatus antivenom. Venom competitive solid-phase enzyme immunoassays and immunoblotting from Argentinean and Paraguayan T. trivittatus populations indicated that antigenic differences exist across the species range. SDS-PAGE showed variations in type and relative amounts of venom proteins between T. trivitattus samples from Argentina and Paraguay. MALDI-TOF mass spectrometry indicated that while some sodium channel toxins are shared, including β-toxin Tt1g, others are population-specific. Proteolytic activity by zymography and peptide identification through nESI-MS/MS also point out that population-specific proteases may exist in T. trivitattus, which are postulated to be involved in the envenoming process. A time-calibrated molecular phylogeny of mitochondrial COI sequences revealed a significant (8.14%) genetic differentiation between the Argentinean and Paraguayan populations, which appeared to have diverged between the mid Miocene and early Pliocene. Altogether, toxinological and genetic evidence indicate that T. trivitattus populations from Paraguay and Argentina correspond to distinct, unique cryptic species, and suggest that further venom and taxonomic diversity exists in synanthropic southern South American Tityus than previously thought.